IEO Report on the Evaluation of the Financial Sector Assessment Program. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2006)
The Financial Sector Assessment Program (FSAP) is a joint IMF-World Bank initiative to provide countries with comprehensive evaluations of their financial systems.The IEO evaluation assessed the effectiveness of the FSAP from the perspective of the IMF. The main findings address the following areas: the nature of priority setting under the FSAP; the efficiency of FSAP processes and quality of the main diagnostic tools; the overall quality of FSAP content; how well the IMF has used FSAP results in its surveillance, technical assistance, and program activities; and evidence on the overall impact of the FSAP on the domestic policy dialogue, changes in policies and institutions, and market participants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet